Effect of Dictation Strategy on Senior Secondary School Student’s Academic Performance in Biology Concepts - Oyakhirome, A. H.; Gbeleke, Lilian A.; Eraikhuemen, L. (NIU Journal of Social Sciences; Vol 11 No 2 (2025): NIU Journal of Social Sciences, Vol. 11 No. 2, June 2025, 2025)
The study is concerned with the effect of Dictation Strategy on Biology student’s Academic Performance, in Egor Local Government Area of Edo State. Two research questions were raised to guide the study and two hypotheses were formulated and tested at 0.05 level of significance. The study employed a quasi-experimental research design, using pre-test post-test non-equivalent control group design. The population of the study comprised of 10500 SS II Biology students in Mixed public Senior Secondary Schools. The sample of the study consists of students in two intact classes randomly selected by balloting from two schools. One intact SS II class of 40 students: 20 boys and 20 girls served as experimental group while the other intact class of 41 students: 20 boys and 21 girls served as control group.  The instrument, Biology Academic Achievement Test (BAAT) was used to collect data and Kuder Richardson formular 20 with an internal consistency coefficient of 0.67 was obtained. The BAAT was used to pre-test both experimental and control group, it was reshuffled and administered as post-test to both groups after the administration of treatment to the experimental group. Paired sample t-test, and ANOVA were used for Data analysis. The findings of the study revealed that there was a significant difference in the post-test and pre-test of students taught concepts of Protista in their Academic Performance using Dictation Strategy and there was no significant interaction effect of Dictation Strategy and sex on Biology students’ Academic Performance. It was recommended among others that Biology teachers should incorporate the use of Dictation Strategy in teaching with other methods because it is capable of improving biology students’ Academic Performance than the conventional method. It was also recommended that professional organization should organize workshops, Seminars and Conferences for Biology Teachers on the use of Dictation Strategy and its benefit. Keywords: Dictation Strategy, Biology, Conventional method, Academic Performance and Protista.